2022
DOI: 10.1039/d1dt04393e
|View full text |Cite
|
Sign up to set email alerts
|

A new type of phosphate-based phosphor Na3CsMg7(PO4)6:Eu2+/Mn2+with high quantum efficiency and high thermostability

Abstract: The Eu2+ ion, with the 4f75d1 electronic configuration, is one of the most important activated ions for its symmetry-allowed 4f→5d electron transition. Herein, we successfully prepared a new type of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Fig. 4(d) presents the decay curves of SLSO: x Bi 3+ monitored under 350 nm excitation and at 550 nm emission, which can be well fitted using the exponential equation: 38 I ( t ) = A 1 exp(− t / τ 1 ) + A 2 exp(− t / τ 2 )where t represents the decay time, A 1 and A 2 represent constants, and τ 1 represents the fast and τ 2 represents the slow decay lifetime. The average lifetime of the activated ion Bi 3+ ( τ av ) can be expressed using the equation: τ av = ( A 1 τ 1 2 + A 2 τ 2 2 )/( A 1 τ 1 + A 1 τ 2 )…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Fig. 4(d) presents the decay curves of SLSO: x Bi 3+ monitored under 350 nm excitation and at 550 nm emission, which can be well fitted using the exponential equation: 38 I ( t ) = A 1 exp(− t / τ 1 ) + A 2 exp(− t / τ 2 )where t represents the decay time, A 1 and A 2 represent constants, and τ 1 represents the fast and τ 2 represents the slow decay lifetime. The average lifetime of the activated ion Bi 3+ ( τ av ) can be expressed using the equation: τ av = ( A 1 τ 1 2 + A 2 τ 2 2 )/( A 1 τ 1 + A 1 τ 2 )…”
Section: Resultsmentioning
confidence: 93%
“…The lifetime values decreased significantly with the increase in the Bi 3+ concentration because the distance between Bi 3+ ions is shortened, increasing the energy transfer rate and altering the probability of excited state energy being absorbed by the luminescent center. 38 In conclusion, the non-radiative transition process…”
Section: Dalton Transactions Papermentioning
confidence: 92%
“…Eu 2+ -doped Na 3 RbMg 7 (PO 4 ) 6 and Na 3 CsMg 7 (PO 4 ) 6 phosphors have been reported lately. However, there is a conflicting viewpoint on which the crystallographic site is suitable for the accommodation of Eu 2+ dopants. Therefore, to probe the actual distribution of Eu 2+ in diverse sites, NAMPO:0.01Eu 2+ (A = K, Rb, and Cs) phosphors are designed and synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the author also found that Na 3 CsMg 7 (PO 4 ) 6 crystals with a large size can be rapidly grown by the high-temperature melting method without flux. Lin-Ying Shi et al 133 prepared Na 3 CsMg 7 (PO 4 ) 6 :Eu 2+ ,Mg 2+ (NCMP:Eu 2+ ,Mg 2+ ). The author inferred that Eu 2+ and Mn 2+ mainly occupied Na + and Mg 2+ sites, respectively, and had blue and red double emission bands under 395 nm light excitation.…”
Section: Eu 2+ As An Excitation Centermentioning
confidence: 99%